أثر الجائحة في عقد الإجارة عند علماء المالكية - د. انتصار المهدي التومي (Aljameai, 1970)
ملخص البحث:        تناول هذا البحث مسألة من مسائل الفقه الإسلامي ألا وهي أثر الجائحة في عقد الإجارة عند علماء المالكية ، وقد بيّنت في هذا البحث معنى الجائحة في اللغة وعند فقهاء المالكية ، وأدلة مشروعية اعتبارها ، وأنواعها ، وأثرها في عقد الإجارة.        وتوصلت هذه الدراسة إلى أن للجائحة أثرا في عقد الإجارة ، فقد يترتب على حدوث الجائحة إنقاص الأجرة بقدر نقصان المنفعة من العين المؤجرة ، أو سقوط الأجرة بأكملها إذا تعذر استيفاء كامل المنفعة، أو تعليق العقد، أو فسخه.Abstract:This research took a place to solve one of the islamic jurisprudence cases which is “The impact of the pandemic on the lease contracts among Malikia scholars”, and in this study I have shown the meaning of “pandemic” in the language, it’s meaning among Malikia scholars, It's legitimate evidence, its kinds, and it’s effect in lease contracts.This study has found that the pandemic has an effect on lease contracts, because the pandemic might cause the fare to decrease by the same amount as the benefit decreases from the rented place or thing (this includes real estate, farms etc) , or dropping the whole fare if the rented place or thing couldn’t be used to its full potential, or suspending the contract, or terminating it.